The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1089/ast.2017.1713
|View full text |Cite
|
Sign up to set email alerts
|

The UK Centre for Astrobiology: A Virtual Astrobiology Centre. Accomplishments and Lessons Learned, 2011–2016

Abstract: The UK Centre for Astrobiology (UKCA) was set up in 2011 as a virtual center to contribute to astrobiology research, education, and outreach. After 5 years, we describe this center and its work in each of these areas. Its research has focused on studying life in extreme environments, the limits of life on Earth, and implications for habitability elsewhere. Among its research infrastructure projects, UKCA has assembled an underground astrobiology laboratory that has hosted a deep subsurface planetary analog pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
0
1
0
1
Order By: Relevance
“…Cockell et al . 57 has suggested that even normal background levels of radiation may be a significant long-term factor in soil systems.…”
Section: Introductionmentioning
confidence: 99%
“…Cockell et al . 57 has suggested that even normal background levels of radiation may be a significant long-term factor in soil systems.…”
Section: Introductionmentioning
confidence: 99%
“…The Science and Technology Facilities Council's (STFC) Boulby Underground Laboratory (BUL) sits at approximately 1,070-1,100 m below ground surface [27,28] within Boulby mine, a potash and polyhalite mine operated by Israel Chemicals Limited, in North Yorkshire. BUL, begun in 1988, was motivated by the search for dark matter [27] and hosts experiments requiring low background radiation conditions [28][29][30][31][32]. The background activity from radionuclide contamination (gamma radiation) is particularly low (approximately 0.1 ppm of uranium and thorium and 1,130 ppm of potassium) [27].…”
Section: The Boulby Underground Laboratorymentioning
confidence: 99%
“…美国NASA天体生物学研究所自 成立之初就要求每个成员机构必须开展本科生/研究 生/博士后教育以及中小学生和公众的科普宣传 [17] . 英 国天体生物学研究中心把教育(大学生和中小学生 等)、培训(中小学教师和航天员等)和公众科普作为其 主要发展方向之一 [116] .…”
Section: 行星开发与行星保护unclassified